2013
DOI: 10.12785/jeps/140102
|View full text |Cite
|
Sign up to set email alerts
|

Level of Organizational Culture at Jerusalem Governorate Secondary Schools as Viewed by Administrators and Teachers

Abstract: This study aims at determining the level of organizational culture at Arab secondary schools in Jerusalem as viewed by administrators and teachers, and was undertaken in 2011. A cluster sample of 21 schools was chosen; 42 administrators and 294 teachers responded to a 61-item validity and reliablity questionnaire. Results showed that the level of organizational culture at the Arab secondary schools as viewed by respondents was "high" in general and in the sets of organizational expectations, beliefs, and value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The findings of the current study are consistent with the results of Al-Enzi (2017), which concluded that both the degree practice and the importance of organizational culture in secondary schools in Hail were high. It is also consistent with the results of the study of Abdeen (2013), which stated that the level of organizational culture was high in the field of values, beliefs, and expectations, but they differed in the field of norms, where they came to a medium degree. Askar (2012) indicated that the areas of organizational culture that this study addressed were organizational values, organizational beliefs, organizational norms, organizational expectations and all of them came at high levels of the application from the viewpoint of teachers in the Gaza Governments that agrees with the findings of this study.…”
Section: -Results and Discussionsupporting
confidence: 91%
“…The findings of the current study are consistent with the results of Al-Enzi (2017), which concluded that both the degree practice and the importance of organizational culture in secondary schools in Hail were high. It is also consistent with the results of the study of Abdeen (2013), which stated that the level of organizational culture was high in the field of values, beliefs, and expectations, but they differed in the field of norms, where they came to a medium degree. Askar (2012) indicated that the areas of organizational culture that this study addressed were organizational values, organizational beliefs, organizational norms, organizational expectations and all of them came at high levels of the application from the viewpoint of teachers in the Gaza Governments that agrees with the findings of this study.…”
Section: -Results and Discussionsupporting
confidence: 91%